2021
DOI: 10.1155/2021/9990465
|View full text |Cite
|
Sign up to set email alerts
|

Study on Development Law of Mining‐Induced Slope Fracture in Gully Mining Area

Abstract: The development law of mining cracks in shallow coal seams under gully topography was used as the research base to analyze the development characteristics of mining cracks in the 5-2 coal mining face of Anshan Coal Mine, and the weak strength was established. The basic top force model under the action of the overburden is the “nonuniformly distributed load beam” structure model. Through similar simulation research and theoretical calculation analysis, the fracture development law of the working face passing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Besides, previous studies have shown that different mining methods (Du and Gao, 2017;Zhou and Yu, 2022), mining parameters (Wang et al, 2020;Qi et al, 2022) and repeated mining of coal seams (Tian et al, 2019;Cheng et al, 2020) also affect the development height of water-conducting fracture zones. Based on a large number of engineering practices, different numerical analysis models (Zhang et al, 2017;Zeng et al, 2022), mechanical theoretical models (Ning et al, 2020;Zhu et al, 2020;Yang et al, 2021;Tan et al, 2022) and monitoring methods (Wang et al, 2016;Mondal et al, 2020) have been successively introduced into the prediction and exploration of the height of water-conducting fracture zones. In addition, some researchers have effectively observed the development of water-conducting fracture zones from the perspective of strain energy (Swift, 2013;Qi et al, 2019;Sainoki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, previous studies have shown that different mining methods (Du and Gao, 2017;Zhou and Yu, 2022), mining parameters (Wang et al, 2020;Qi et al, 2022) and repeated mining of coal seams (Tian et al, 2019;Cheng et al, 2020) also affect the development height of water-conducting fracture zones. Based on a large number of engineering practices, different numerical analysis models (Zhang et al, 2017;Zeng et al, 2022), mechanical theoretical models (Ning et al, 2020;Zhu et al, 2020;Yang et al, 2021;Tan et al, 2022) and monitoring methods (Wang et al, 2016;Mondal et al, 2020) have been successively introduced into the prediction and exploration of the height of water-conducting fracture zones. In addition, some researchers have effectively observed the development of water-conducting fracture zones from the perspective of strain energy (Swift, 2013;Qi et al, 2019;Sainoki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the pillar under peaceful terrain, when the ore bed is located in the valley terrain area, the study of pillar stability has its particularity [ 40 , 41 , 42 ]. Next, the influence of the spatial relationship of goaf and valley on the stability of the pillar is studied.…”
Section: Parameter Influence Analysismentioning
confidence: 99%
“…Zhang et al (2022b) divided fissures in a valley mining area into dynamic in-plane fissures and boundary fissures, revealing the contraction and closure characteristics of the dynamic in-plane fissures. Yang et al (2021) and Li J. W. et al (2022) analyzed the development characteristics of mining-induced fissures in a valley region and divided the overlying strata into three zones: the collapse fissure zone, the compacted fissure zone, and the vertical fissure zone. Li et al (2019) and Wang et al (2021) analyzed the mechanism of mine pressure manifestation and its mutual influence on surface geological hazards, revealing that the variation of stress in the gully area is among the necessary conditions for the occurrence of working face impact pressure.…”
Section: Introductionmentioning
confidence: 99%